MEDIASI KELUARGA SEBAGAI INSTRUMEN PENYELESAIAN KONFLIK RUMAH TANGGA: ANALISIS NORMATIF DAN PSIKOLOGIS - Ahmad Burhanuddin; Mulizawati Harmawati; Herman Radiansyah; Junaidi Affandi (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
Family mediation constitutes an alternative instrument for resolving domestic conflicts that emphasizes a dialogical and reconciliatory approach rather than rigid litigation procedures. This study aims to analyze the position of family mediation from both normative and psychological perspectives by examining the relevant legal regulations and their implications for the mental well-being of the parties involved. Normatively, the research is grounded in Law Number 1 of 1974 as amended by Law Number 16 of 2019 on Marriage, Law Number 23 of 2004 on the Elimination of Domestic Violence, and Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures. From a psychological standpoint, mediation is viewed as capable of reducing tension, enhancing communication, and maintaining the continuity of family relationships. The findings indicate that family mediation has the potential to serve as a humane dispute resolution mechanism; however, its effectiveness remains constrained by limited legal awareness, a lack of professional mediators, and insufficient psychological protection for vulnerable parties. Strengthening regulatory frameworks and integrating psychosocial support are therefore necessary to ensure that family mediation functions as an adaptive and equitable legal instrument.